Graduate unemployment in South Africa: Perspectives from the banking sector - Faith Oluwajodu; Derick Blaauw; Lorraine Greyling; Ewert P.J. Kleynhans (SA Journal of Human Resource Management, 2015)
Orientation: South Africa is experiencing growth in its graduate labour force, but graduateunemployment is rising with the overall unemployment rate. Graduate unemployment isproblematic, because it wastes scarce human capital, which is detrimental to the economy inthe long run.